(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background: Medical ethics and professionalism have been included in the competencies which an Indian medical graduate should achieve to become globally relevant. This study was done to describe medical ethics and professionalism and explore the factors affecting it, among the medical students in India. Methods: A cross-sectional study was conducted among undergraduate medical students of India in 2022; data were collected using google documents and analyzed using SPSS v20.0. Results and Conclusion: Two thirds of the participants were aware of the principles of medical ethics. Medical college lectures/seminars were the source of ethics for majority of the participants. Around 32.2% had conflicts in their medical school. Though 99.6% of the participants opined that the patient deserve respect, only one third (34.3%) opined that medical errors should be shared to the patients. Prevalence of consumption of alcohol, smoking, drugs among medical students were 5.6%, 3.1% and 0.7% respectively.